ANALISA PERBANDINGAN HUBUNGAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA BADAN PEMBERDAYAAN MASYARAKAT PEMERINTAHAN DESA KABUPATEN BOGOR DAN DISPENDA KOTA BOGOR - Isman Kadar (MAGMA : JURNAL MAGISTER MANAJEMEN, 2015)
The purpose of this study was to determine the relationship of motivation on employee performance employee Village Community Empowerment Board Governance Dispenda Bogor and Bogor City. The study population was all employees Dispenda Bogor City with samples are 114 employees and employees of the Agency for Community Empowerment Bogor Regency Village Government with a sample of 121 employees. The research instrument was a questionnaire. Collected data is processed using correlation analysis technique.The results show that: of First, the relationship between work motivation and performance korelasiry.2 coefficient = 0.507 rtabel (rtabel = 0.176 at ? = 0.05 and rtabel = 0.230 at ? = 0.01). Relations were significant for Sig = 0.000 This value is identical to the p-value, where the p-value is smaller than ? (0.05). That is, there is a positive and significant relationship between motivation and employee performance Employees Community Empowerment Board Bogor Regency Village Government.Secondly there is a relationship work motivation and performance of employees, the value of the relationship is 0.673. The direction of the relationship is 'positive' and the degree of relationship 'strong' as the value of the relationship is between the value of the relationship 0.673 from 0.60 to 0.799. Figures probability or Sig. (2-tailed) was 0,000 less than 0.05, which means the relationship work motivation and employee performance employee Revenue Bogor City is 'significant' at a significance level of 0.01 or 0.05 or 99% and 95%.Keywords: Work Motivation and Employee Performance